The road to monetary union in Europe : the emperor, the kings, and the genies - Padoa-Schioppa, Tommaso (Oxford : Clarendon Press, 1994)
An indispensable guide to the economic, political, and diplomatic process that led to the creation of the European single market and the signing of the Maastricht Treaty. The author, a protagonist in the monetary affairs of the Community for more than a decade, lucidly assesses the opportunities and risks involved in economic and monetary integration. A central theme of the book is the proposition that a group of sovereign countries cannot for long sustain free trade, unrestricted capital movements, fixed exchange rates, and full autonomy of national macroeconomic policies, and so need to move towards monetary union and a single currency. The author discusses extensively such issues as the single currency, the tasks of a European central bank, the ECU, the role of budgetary rules, currency competition, and the relationship between EMU and political union.
The author has created an insider's guide to this topical issue for students, academics, policymakers and commentators alike. The book contains extracts from official EC documents dealing with EMU and an extensive chronology which will be of particular use to readers.
1. Rules and Institutions in Multi-Country Economies -- 2. Capital Mobility: Why is the Treaty not Implemented? -- 3. Lessons from the European Monetary System -- 4. The ECU's Coming of Age -- 5. After the Single European Act: Efficiency, Stability, and Equity -- 6. The EMS is not Enough: The Need for Monetary Union -- 7. The Delors Report: From Intentions to Action -- 8. Monetary Union and Competition -- 9. Fiscal Compatibility and Monetary Constitution -- 10. Monetary Union and Political Union -- 11. On the Eve of Maastricht -- 12. Agenda for Stage Two -- Appendix 3. Conclusions of the European Council: 1988-1991 -- Appendix 4. Economic and Monetary Union in the Treaty of Maastricht -- Appendix 5. Protocol on the Statute of the European System of Central Banks and of the European Central Bank.
Includes bibliographical references (p. [273]-280.) and index.
Keywords: European Monetary System (Organisation); Monetary policy -- European Economic Community countries